Enhanced nitrate-nitrogen removal by modified attapulgite-supported nanoscale zero-valent iron treating simulated groundwater. (1st May 2018) - Dong, Lei; Lin, Li; Li, Qingyun; Huang, Zhuo; Tang, Xianqiang; Wu, Min; Li, Chao; Cao, Xiaohuan; Scholz, Miklas
Abstract: Attapulgite (or palygorskite) is a magnesium aluminium phyllosilicate. Modified attapulgite-supported nanoscale zero-valent iron (NZVI) was created by a liquid-phase reduction method and then applied for nitrate-nitrogen (NO3 -N) removal (transformation) in simulated groundwater. Nanoscale zero-valent iron was sufficiently dispersed on the surface of thermally modified attapulgite. The NO3 -N removal efficiency reached up to approximately 83.8% with an initial pH values of 7.0. The corresponding thermally modified attapulgite-supported nanoscale zero-valent iron (TATP-NZVI) and NO3 -N concentrations were 2.0 g/L and 20 mg/L respectively. Moreover, 72.1% of the water column NO3 -N was converted to ammonium-nitrogen (NH4 -N) within 6 h. The influence of environmental boundary conditions including dissolved oxygen (DO) concentration, light illumination and water temperature on NO3 -N removal was also investigated with batch experiments. The results indicated that the DO concentration greatly impacted on NO3 -N removal in the TATP-NZVI-contained solution, and the NO3 -N removal efficiencies were 58.5% and 83.3% with the corresponding DO concentrations of 9.0 and 0.3 mg/L after 6 h of treatment, respectively. Compared to DO concentrations, no significant (p > 0.05) effect of light illumination on NO3 -N removal and NH4 -N generation was detected. The water temperature also has great importance concerning NO3 -N reduction, and the removal efficiency of NO3 -N at 25 °C was 1.25 times than that at 15 °C. For groundwater, therefore, environmental factors such as water temperature, anaerobic conditions and darkness could influence the NO3 -N removal efficiency when TATP-NZVI is present. This study also demonstrated that TATP-NZVI has the potential to be developed as a suitable material for direct remediation of NO3 -N-contaminated groundwater. Graphical abstract: Image 1 Highlights: Thermal modification increases the specific surface area of purified attapulgite. The NO3 -N removal by TATP-NZVI reached up to 83.8% after 6 h of reaction. Reduction was the main approach for NO3 -N removal by TATP-NZVI. Water temperature and DO concentration significantly impact on NO3 -N removal. Key removal technologies of NO3 -N in groundwater with TATP-NZVI were highlighted.